Pengaruh Penerapan Green Accounting Dan Kinerja Lingkungan Terhadap Kinerja Keuangan Perusahaan Manufaktur Sub Sektor Logam Dan Sejenisnya Yang Terdaftar Di Bursa Efek Indonesia - Hayaah, Aurellia Nur (Jurnal KIAFE, 2023)
Financial performance is a company goal, namely a description of the company's ability to increase profits by generating profits. This research is also motivated by the low number of companies implementing green accounting in Indonesia and many companies that do not receive a PROPER rating or do not participate in the PROPER rating. The independent variables used in this research are green accounting and environmental performance. Meanwhile, the dependent variable in this research is the company's financial performance as measured by Return On Assets (ROA). The population of this research was 17 companies in the metals and similar sub-sectors listed on the Indonesian Stock Exchange (BEI) for the 2016-2021 period. The sample was determined using a purposive sampling method to obtain a sample of 8 companies or 48 research samples. The research method used in this research is descriptive analysis method with multiple linear regression analysis and using SPSS version 25 measuring instruments. The research results show that partially green accounting and environmental performance do not have a significant positive effect but simultaneously green accounting and environmental performance have a positive effect significant to the company's financial performance.